Procesno utemeljeno modeliranje erozije tal - Petkovšek, Gregor (Acta hydrotechnica, 2000)
The paper presents an overview of process based methods for soil erosion modelling. In the introduction, the history and the reasons for soil erosion modelling in the fields of agriculture and civil engineering are given. Then an overview of erosion processes, modelling concepts and equations follow. The processes of rill and interrill erosion, splash erosion, detachment and transport capacity of overland and rill flow, and channel initiation are described. The interrelations between the processes and the corresponding mathematical formulations are explained. Further, the paper presents and comments on the traditional methods used for soil erosion prediction, such as USLE and the Gavrilović equation. Also, three recently developed process based models are presented: the American WEPP, the Hollandese LISEM and the Australian TOPOG model. The structure of the models is emphasized, as well as the processes incorporated. The aims and possible applications are described
Keywords: distributed models; erozija tal; modeli s porazdeljenimi spremenljivkami; odplavljanje; procesno utemeljeno modeliranje; process based modelling; sediment yield; soil erosion